Musharraf's skewed Line of fire - Bhasin, R. V. (Mumbai : National Publications, 2007)
Critical analysis of In the line of fire, an autobiography of Pervez Musharraf, former president of Pakistan.
Keywords: Musharraf, Pervez; Pakistan -- Politics and government -- 1988-